2018
DOI: 10.7717/peerj.4549
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an ophthalmic formulation of polyhexamethylene biguanide in gamma-sterilized and ethylene oxide sterilized low density polyethylene multidose eyedroppers

Abstract: BackgroundPolyhexamethylene biguanide (PHMB) eye drops are a frequently used medication to treat Acanthamoeba keratitis. In the absence of marketed PHMB eye drops, pharmacy-compounding units are needed to prepare this much needed treatment, but the lack of validated PHMB stability data severely limits their conservation by imposing short expiration dates after preparation. In this study we aim to assess the physicochemical and microbiological stability of a 0.2 mg/mL PHMB eye drop formulation stored in two kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, this could decrease ophthalmic tolerance, especially for paediatric patients, which is the target population for which these formulations are designed. In the formulations we tested, the pH was buffered to a more physiological value (around pH 6), thus hopefully limiting potential unpleasantness for the children during administration and therefore increasing therefore adherence to treatment as well as suppressing any potential modifications of pH that have already been reported during the use of gamma-sterilized LDPE eyedroppers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this could decrease ophthalmic tolerance, especially for paediatric patients, which is the target population for which these formulations are designed. In the formulations we tested, the pH was buffered to a more physiological value (around pH 6), thus hopefully limiting potential unpleasantness for the children during administration and therefore increasing therefore adherence to treatment as well as suppressing any potential modifications of pH that have already been reported during the use of gamma-sterilized LDPE eyedroppers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, few studies have been published concerning atropine eyedrops stability, but the analyses were either lacking several tests or suffered from shortcomings concerning breakdown product research [ 24 , 25 , 26 ]. As single-dose container technology is not readily available to compounding pharmacies, multidose eyedroppers (often in low dose polypropylene) are the most used container and therefore the most studied [ 27 , 28 , 29 , 30 ]. However, not all of those devices possess a system allowing their content to be preservative-free, and their contents must therefore be preserved.…”
Section: Introductionmentioning
confidence: 99%
“…If the affinity of this form of VA is higher for CZ than for HPCD, it would preferentially associate with CZ and precipitate instead of being complexed by the HPβCD. In addition, it has been shown that an interaction is possible between the contents and the container for some LDPE packaging articles sterilized with gamma rays, leading to acidification of the eye drops [ 57 ]; in our case, this acidification could lead us below our pH limit and therefore lead to precipitation if the buffering capacity is exceeded.…”
Section: Discussionmentioning
confidence: 93%
“…The effective antibacterial activity of PU-PHMG was attributed to the bactericidal capacity of PHMG. The interaction between PHMG and the anionic components of bacterial cell wall compromises membrane integrity, further causing cell membrane rupture and leads to microbial death [ 53 , 54 ]. The inhibition rates of PU-(PHMG/HA) 5 /5-5 on E. coli , P. aeruginosa , and S. aureus were 99.99%, 99.96%, and 99.99%, respectively, indicating that the film had outstanding antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%